Actuator design for data storage systems - Thong, Chee Sheng. (2008)
The friction at the pivot bearing and the mechanical resonance of the head actuator are the two of the major sources that limit the data processing speed and accuracy in hard disk drives (HDDs). The mechanical resonance is typical micro actuators exhibit a very lightly damped resonance frequency.